Effects of mixing time and nano silica on some properties of superfine-tailings cemented paste backfill. (16th May 2023) - Hu, Yafei; Li, Keqing; Zhang, Bo; Han, Bin
Graphical abstract: Highlights: The optimal mixing time makes the strength and fluidity of SCPB reach the best. The mixing time can change the degree of influence of NS on thixotropy. NS can catalyze the hydrolysis of gypsum and generate more hydration products. NS reacts with CH to form C-S-H gel with low C/S and H/S. Abstract: The use of solid waste for filling is an important direction for sustainable development in underground mines. In order to achieve efficient recycling of superfine tailings, mechanical test, slump test, rheological test and microscopic test are conducted to investigate the mechanism of mixing time on the properties of Nano-SiO2 (NS)-doped superfine-tailings cemented paste backfill (SCPB). The results show that the fluidity and uniaxial compressive strength (UCS) of SCPB tends to increase and then stabilize or decrease with the prolongation of mixing time, and there is an optimal mixing time to make the properties of SCPB reach the best state. The mixing time and NS dosage have the most significant effect on the early UCS of SCPB, and the effect decreases with the increase of the curing time. The UCS tended to increase and then decrease with increasing NS dosage, and the UCS of SCPB has a maximum value when the NS dosage is 2%. The results of microscopic analysis show that the degree of hydrolysis of C3 S in SCPB gradually increases as the mixing time reaches the optimum. The appropriate NS dosage can play a catalytic role to promote the hydrolysis of gypsum and increase the amount of hydration products produced. The addition of NS in SCPB generates a more structurally stable C-S-H gel with lower Ca/Si and H2 O/Si and longer average silicon chain length, which enhances the UCS of SCPB. The results of the study can provide guidance for the efficient filling of superfine tailings.